Control and operation of grid-connected wind farms : major issues, contemporary solutions, and open challenges /: major issues, contemporary solutions, and open challenges. (2016) - Jiang, John N; Tang, Choon Yik; Ramakumar, R (Ramachandra), 1936-
No abstract available